2015
DOI: 10.15376/biores.10.2.2094-2102
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics of Teak Wood Attacked by Neotermes tectonae

Abstract: The teak trees in certain areas of Java Island are frequently attacked by Neotermes tectonae termites. Trees attacked by this species have a tumor-like growth in the stem that can be easily identified in the field. This study evaluated the chemical properties of the attacked wood. Based on a visual inspection, the type of attacks were classified as either type I, if included phloem was formed in the heartwood, or type II, which was distinguished by the softened and hollowed areas in the heartwood. For each typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Lignin content in teak wood ranges from 30 to 43% [28][29][30][31]. Unmodified (reference) wood in this work has lignin content within this range (35.42%), as reported previously [32].…”
Section: Klason and Dioxane Lignin Yieldssupporting
confidence: 81%
“…Lignin content in teak wood ranges from 30 to 43% [28][29][30][31]. Unmodified (reference) wood in this work has lignin content within this range (35.42%), as reported previously [32].…”
Section: Klason and Dioxane Lignin Yieldssupporting
confidence: 81%
“…In addition, there are numerous causes for the formation of wood figures or burls, including congenital growth condition, growth rate and size of trees, postnatal climate, soil, geographic location, height above sea level, latitude, and biological and non-biological effects, such as the wounds caused by insects, animals, or out-side disasters, cellular morphology, arrangement influenced by ambient temperature and humidity changes, natural disasters, invasive infection of pathogens, variation of tree genes, a lack of phytohormones, or other unknown effects (Black, 1945;Kelly and Black, 1949;Black, 1952a and1952b;Millington, 1954a and1954b;Ahuja, 1962;de Torok, 1968;Beals and Davis, 1977;Eklund and Säll, 2000;Dodueva et al, 2007;Schweingruber, 2007;Lukmandaru, 2015). White and Millington (1954a) mentioned that the Picea glauca burl grows in coastal regions with salt mist.…”
Section: C Age Estimation Of Taiwan Cypress Bwfsmentioning
confidence: 99%
“…Previous reports demonstrated that deoxylapachol effectively inhibited the growth of some fungi (Sumthong et al 2006(Sumthong et al , 2008Lukmandaru 2013). Thus, the formation of included phloem might be related to the Neotermes tectonae termite attacks (Lukmandaru 2015).…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…One of the studies has adressed the decay resistance of the included phloem in Koompassia excelsa wood and has compared it to the normal tissues (Wong 1988). Our previous works have explored the chemical characterization of abnormal wood in teak Lukmandaru 2011;Lukmandaru 2015). Therefore, this study investigated the colour and chemical properties of the included phloem stem wood in radial direction.…”
Section: Introductionmentioning
confidence: 99%